Influence of graphene on fire protection of intumescent fire retardant coating for steel structure - Wang Zhan; Le Chen; Zhaozhan Gu; Juncheng Jiang (Energy Reports, 2020)
Graphene (GR) was used as filler to improve the performance of fire resistance, thermal stability, smoke suppression of waterborne intumescent fire-retardant coating. The influence of graphene (GR) on the properties of the intumescent fire-retardant coating was studied by fire protection test, TGA, SEM and smoke density test. The results showed that the GR can effectively enhanced the performance of fire resistance and thermal stability of the coating. The result of SEM test indicated the coating with GR had excellent intumescent effect and enhanced foam structure. The smoke density test of the coating demonstrated the coating contain GR had excellent performance of smoke suppression.
Keywords: 330; Graphene; Fire resistance; Coating; Steel structure